CALCUL MECANIQUE ET ELECTRIQUE DES LIGNES AERIANES DE TRANSPORT ELECTRIQUE HAUTE TENSION - ETTIR AOUNALLAH; BOUKRARA WALID; DJEKIDEL Rabah (UNIVERSITE Amar Telidji de Laghouat.FACULTE DE TECHNOLOGIE.DEPARTEMENT D’ELECTROTECHNIQUE, 2022)
The overhead transport network plays a key role in the transport of electrical energy from the production center to the consumption place at high and very high voltage. Conductors must meet several design criteria. This memory deals with a study of mechanical and electrical dimensioning of a very high voltage overhead line. A mechanical dimensioning was carried out; it consists in determining the installation parameters, such as the maximum sag, the mechanical tension of the conductor, the charges acting on the conductor due to climatic constraints. An electrical dimensioning was also carried out in order to calculate the different electrical parameters of the phase conductor, based on a mathematical modeling of the performance of an overhead line from the power flow through this transmission line, the calculation of the electric and magnetic fields, as well as the evaluation of the corona effect and the losses produced.
Option : Electromécanique